2004
DOI: 10.3177/jnsv.50.161
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Mulberry Leaf Extract on Postprandial Hyperglycemia in Normal Rats

Abstract: We examined the inhibitory effects of aqueous ethanol extract from mulberry leaves (ME) on postprandial hyperglycemia in normal Wistar rats. ME dose-dependently sup pressed the postprandial rise of blood glucose in rats, when ME (0.02-0.5g/kg) was given

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 9 publications
2
62
0
1
Order By: Relevance
“…They are widely used in processed foods that have been developed to prevent lifestyle-related diseases. The leaf extract of Morus alba (LEM) also has a suppressive effect on postprandial glucose [1][2][3]. However, the interactions between LEM and prescribed medicines, and the resulting effects on postprandial glucose and insulin, have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are widely used in processed foods that have been developed to prevent lifestyle-related diseases. The leaf extract of Morus alba (LEM) also has a suppressive effect on postprandial glucose [1][2][3]. However, the interactions between LEM and prescribed medicines, and the resulting effects on postprandial glucose and insulin, have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, the interactions between LEM and prescribed medicines, and the resulting effects on postprandial glucose and insulin, have not yet been investigated. LEM markedly suppressed postprandial glucose and insulin in healthy subjects and normal rats [1][2][3], and Mudra et al reported that mulberry suppressed blood glucose after sucrose administration in diabetic subjects [4]. Furthermore, the appearance of polyuria and the elevation of fasting blood glucose and insulin were delayed by the daily intake of LEM in diabetic mice [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(kuwa), 5) and as strong as that of Salacia oblonga (sarashia) 6) and Psidium guajava (guava), 7) which are well-known -glucosidase inhibitors. In the experiment in vivo, the PsEx concentration in the intestines administrated at 1,400 mg/kg was 42 mg/ml, much higher than the in vitro maltase inhibitive activity test.…”
Section: Inhibitory Effects Of Pasuchaca (Geranium Dielsiaum) Extractmentioning
confidence: 99%
“…The present study shows the effect of pasuchaca (Geranium dielsiaum) as an -glucosidase inhibitor. [4][5][6][7] Pasuchaca is a plant that thrives naturally in the Peruvian Andes, and it has been used as traditional medicine for the treatment of diabetes in South America, but scientific evaluation is still lacking. To clarify its mechanism of action, the inhibitory effect of pasuchaca methanolic extract (PsEx) on postprandial blood glucose elevation was evaluated in vivo.…”
Section: Inhibitory Effects Of Pasuchaca (Geranium Dielsiaum) Extractmentioning
confidence: 99%